1969
DOI: 10.1111/j.1440-1754.1969.tb02812.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Children and Adolescents on Queensland Aboriginal Settlements, 1967*

Abstract: In this survey of health in Aboriginal children on 12 settlements and missions in Queensland, the reported births and deaths suggest an infant mortality rate six times higher than the Queensland average, with diarrhoeal disease, respiratory infection, and diseases of the neonatal period accounting for 75% of infant deaths. Children in the post‐weaning period showed retardation of growth, anaemia, and frequent respiratory or enteric infection. The prevalence of hookworm infection has, on the evidence of this an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…Horsfall (1957) reported an elevation of the ESR in unusually large numbers of Aborigines in contrast to other racial groups in North Queensland, and Galbraith (1967) could find no clinical expianation for this in the majority of those examined. A high ESR was present in half the children tested on 12 widely scattered settlements throughout Queensland (Jose, Self and Stallman, 1969), and the preliminary part of this study confirmed these observations.…”
Section: Characteristics Of Three Selected Groupssupporting
confidence: 83%
See 2 more Smart Citations
“…Horsfall (1957) reported an elevation of the ESR in unusually large numbers of Aborigines in contrast to other racial groups in North Queensland, and Galbraith (1967) could find no clinical expianation for this in the majority of those examined. A high ESR was present in half the children tested on 12 widely scattered settlements throughout Queensland (Jose, Self and Stallman, 1969), and the preliminary part of this study confirmed these observations.…”
Section: Characteristics Of Three Selected Groupssupporting
confidence: 83%
“…reported a high incidence of cardiac murmurs, elevated erythrocyte sedimentation rates (ESR) in asymptomatic children, and unusually high titres of antistreptolysin (ASOT), in Australian Aboriginal children at two remote missions in North Queensland. A survey of Aboriginal children and adolescents in Queensland in 1967 (Jose, Self and Stallman, 1969) confirmed the high rate of organic and non-organic cardiac murmurs, found widespread chronic and recurrent respiratory and skin infections, a high incidence of rheumatic fever, and many children with asymptomatic proteinuria and haematuria. Unusual features of rheumatic fever in these areas (unpublished data) were the mild systemic reaction, the rarity of arthritis and the number of cases presenting with a mitral pansystolic murmur and a history of vague chronic illness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…also estimated that the Indigenous infant mortality rate was six times higher than the overall Queensland rate. Of 133 infant and 32 childhood deaths in eight communities between 1962 and 1966, the most common causes were: gastroenteritis, pneumonia, congenital malformations, prematurity, birth trauma, other neonatal diseases and meningitis . Children in the post‐weaning period showed retardation of growth, anaemia, intestinal parasites and frequent respiratory and enteric infections.…”
Section: Early Descriptive Studiesmentioning
confidence: 99%
“…Among school age children, middle ear disease with hearing loss and rheumatic heart disease were major problems. As noted by the authors, many of these health problems would only respond to improvements in housing, diet and education, ‘all of which involve time, money and legislative and administrative action’ …”
Section: Early Descriptive Studiesmentioning
confidence: 99%